Effects of aging state on fatigue properties of 6A01 aluminum alloy. Issue 6 (3rd April 2022) - Gong, Baishan; Zhang, Zhenjun; Duan, Qiqiang; Qu, Zhan; Hou, Jiapeng; Zhang, Zhefeng
Abstract: The high‐cycle fatigue (HCF) experiments were carried out for different aging states to study the effects of the aging state and yield strength on the fatigue properties of a 6A01 Al alloy. The results show that the 6A01 Al alloy with the highest yield strength at a peak‐aging (PA) state can exhibit the highest fatigue strength in comparison with the overaged (OA) state and the underaged (UA) state. The main reason is that the increased strength of the 6A01 Al alloy at the PA state can improve the plastic deformation resistance and inhibit the fatigue crack initiation. Additionally, the UA has a similar yield strength but a higher fatigue strength compared with the OA, which shows that the aging state also has a significant influence on the fatigue properties. Finally, combined with the previous studies on the 2XXX and 7XXX Al alloys, the effects of the aging state and yield strength on the fatigue properties of Al alloys are summarized.